Preliminary response to Tislelizumab plus chemotherapy drugs in patient with periampullary carcinoma: a report of one case and a literature review - Tang, Chuanyun; Kong, Yijie; Xu, Lifan; Duan, Chongxu; Fu, Xiaowei; Fang, Lu; Liang, Bo (Frontiers in Immunology, 2024)
Periampullary carcinoma is a malignant gastrointestinal tumor originating from the head of the pancreas, distal bile duct, duodenum, or the ampulla of Vater. Currently, surgery remains the primary treatment option, yet the postoperative recurrence rate remains high. Chemotherapy is the main approach for controlling postoperative recurrence.Histologically, periampullary carcinoma is categorized into two types: intestinal (IN) and pancreaticobiliary (PB) subtype. Each subtype requires different therapeutic approaches, with the PB type primarily treated with gemcitabine and the IN type with 5-FU. Despite these options, patient outcomes are still unsatisfactory. In recent years, the feasibility of immunotherapy in tumour treatment has been increasingly evidenced, although research on its efficacy in periampullary carcinoma treatment is still limited. In this report, we present a case of a periampullary carcinoma patient who experienced recurrence and metastasis after undergoing radical pancreatoduodenectomy and receiving gemcitabinebased chemotherapy post-surgery. Through next-generation sequencing (NGS), we identified high expression levels of programmed cell death-ligand 1 (PD-L1) with a combined positive score (CPS) of 35, high tumor mutation burden (TMB-H), and high microsatellite instability (MSI-H) in this patient. Therefore, we implemented a combination therapy using Tislelizumab and chemotherapy. According to the latest follow-up, the tumors are effectively controlled. Our utilization of immunotherapy combined with chemotherapy holds significant implication for the treatment of periampullary carcinoma.